2011
DOI: 10.1088/2041-8205/730/2/l22
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration, Magnetic Fluctuations, and Cross-Field Transport of Energetic Electrons in a Solar Flare Loop

Abstract: Plasma turbulence is thought to be associated with various physical processes involved in solar flares, including magnetic reconnection, particle acceleration and transport. Using Ramaty High Energy Solar Spectroscopic Imager (RHESSI) observations and the X-ray visibility analysis, we determine the spatial and spectral distributions of energetic electrons for a flare (GOES M3.7 class, April 14, 2002 23:55 UT), which was previously found to be consistent with a reconnection scenario. It is demonstrated that bec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 48 publications
6
90
0
Order By: Relevance
“…These values are in good agreement with what has been found for a few events by Kontar et al (2011) and Guo et al (2012). In their work, Xu et al (2008) modelled the transport of electrons on the basis of a standard collisional transport model.…”
Section: −Febsupporting
confidence: 86%
“…These values are in good agreement with what has been found for a few events by Kontar et al (2011) and Guo et al (2012). In their work, Xu et al (2008) modelled the transport of electrons on the basis of a standard collisional transport model.…”
Section: −Febsupporting
confidence: 86%
“…However, the displacements we found between the metric sources and the flaring loops appear too large (55−300 ) to be interpreted in terms of cross-field transport of the energetic electrons. For example, Kontar et al (2011) found that the cross-field transport of electrons with energies 8−25 keV in a flaring loop yielded excursions that were not larger than 1−2 .…”
Section: Discussionmentioning
confidence: 99%
“…also demonstrated that reconnection in twisted loops with magnetic field convergence near footpoints could provide a configuration for particle re-acceleration in the lower corona and chromosphere (Brown et al 2009). They also show that the developed model can explain some features of the variation in hard X-ray sources recently observed with RHESSI (Kontar et al 2011). used the model developed in Hood et al (2009) and to study particle acceleration in twisted loops using the test-particle approach.…”
Section: Introductionmentioning
confidence: 91%